2018
DOI: 10.1177/1465116517752870
|View full text |Cite|
|
Sign up to set email alerts
|

If you can beat them, confront them: Party-level analysis of opposition behavior in European national parliaments

Abstract: This article explains the variation in opposition behavior by investigating parliamentary voting of opposition parties across 16 European national parliaments. It finds that features of an opposition party that increase its likelihood of winning office in future elections—its size and experience in government—increase the party’s tendency toward confrontation with the government, as do features that increase the party’s need to differentiate itself from the government. At the systemic level, features that incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…Finally, it must be pointed out that model 2 presents no evidence that party features that determine opposition parties’ ability to challenge the government influence their behavior. In analyzing a cross section of 16 European countries, Tuttnauer (2018) shows larger parties and ones with more government experience to be more confrontational and attributes this tendency to their enhanced ability to challenge the government. In the Israeli case investigated in the present study, however, these features did not produce a significant effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it must be pointed out that model 2 presents no evidence that party features that determine opposition parties’ ability to challenge the government influence their behavior. In analyzing a cross section of 16 European countries, Tuttnauer (2018) shows larger parties and ones with more government experience to be more confrontational and attributes this tendency to their enhanced ability to challenge the government. In the Israeli case investigated in the present study, however, these features did not produce a significant effect.…”
Section: Resultsmentioning
confidence: 99%
“…Following Tuttnauer (2018), several party features were incorporated into the analysis, all of them tapping a party’s ability to challenge the government. Seat share is the number of seats held by a party, divided by the total seats in parliament.…”
Section: Methodsmentioning
confidence: 99%
“…Prior research has demonstrated that minority governments will search for support among opposition parties, will be more hesitant to put controversial decisions to a vote, and are less likely to resort to the use of force than majority governments (Prins and Sprecher, 1999;Oktay, 2018;Wagner, 2018). Moving away from the minority-majority dichotomy, Mújica and Sánchez-Cuenca (2006) found that the levels of parliamentary consensus varied according to the size of the government relative to the size of the opposition, while the analysis of Tuttnauer (2018) showed that surplus coalitions take more controversial decisions. Beasley and Kaarbo (2014: 735), in turn, concluded that the overall level of parliamentary support has more impact on the foreign policy of parliamentary democracies than the difference between majority and minority governments, while Palmer et al (2004: 13) showed a significant positive effect of the percentage of seats held by the government on the dispute involvement of parliamentary democracies.…”
Section: Structural and Situational Weakness Of The Governmentmentioning
confidence: 99%
“…Second, aggregated voting behavior on the party level allows us to study government−opposition dynamics and the competitive strategies opposition parties choose vis-à-vis the government (e.g. Andeweg 2013;Hohendorf et al 2018;Tuttnauer 2018). Third, the data allows a longitudinal analysis of party unity in the Bundestag and can thus contribute to the large body of literature that seeks to explain high levels of voting unity in legislatures as well as determinants of its variation (e.g.…”
Section: Possible Research Questionsmentioning
confidence: 99%
“…We can also compare the topics on the roll-call agenda (Figure 4) with the broader policy agenda (for example, as measured in the German Policy Agendas Project, Breunig 2014) to study how political parties shape the legislative agenda. Secondly, aggregated voting behavior at the party level allows us to study government−opposition dynamics and the competitive strategies opposition parties choose vis-à-vis the government (for example, Andeweg 2013; Hohendorf, Saalfeld and Sieberer 2018; Tuttnauer 2018). Thirdly, the data allow a longitudinal analysis of party unity in the Bundestag and can thus contribute to the large body of literature that seeks to explain high levels of voting unity in legislatures as well as determinants of its variation (for example, Carey 2007; Coman 2015; Kam 2009; Saalfeld 1995b; Sieberer 2006; for a first analysis of our data with regard to party unity, see Bergmann et al 2016).…”
Section: Possible Research Questionsmentioning
confidence: 99%